Optimizing the Role of Information Technology in Improving the Work Discipline of Language Center Employees - Trisninawati; Zaid Amin; Sulaiman Helmi; Destina Paningrum (Jurnal Penelitian Pendidikan IPA, 2023)
Employee discipline is a very important factor in achieving the desired organizational goals and needs to be evaluated and improved. This study aims to explain the optimization of the role of Information and Communication Technology (ICT) to improve employee work discipline at the Language Center of South Sumatra Province. The survey method was used in this study by taking a random sample of 10 respondents from the population of employees of the Language Center of South Sumatra Province who were selected by purposive sampling technique. The collected data were analyzed using descriptive statistical techniques and simple linear regression. The results of the study show that overall, the work discipline of employees at the South Sumatra Province Language Center is at a good level. However, several factors such as information technology capabilities, especially in optimizing the use of fingerprint attendance machines, work motivation, supervision, and work environment affect employee work discipline. This study recommends increasing work motivation and more effective supervision to improve employee work discipline by optimizing the use of information and communication technology that already exists at the Language Center of South Sumatra Province. Optimizing the use of information technology, especially in the use of fingerprint attendance machines, can significantly increase employee productivity and performance as well as improve the performance of the South Sumatra Province Language Center in providing better services to the community.